CHANGE OF CHARACTER OF CANDIDATES FOR CIVIL SERVANTS OF MINISTRY OF TRANSPORTATION AFTER FOLLOWING CHARACTER BUILDING COURSE - Dyan Apriyani; Giri Kurnia Widyasari (IKIP Siliwangi Bandung, 2019)
The construction of the character has long been echoed by the first president of the Republic of Indonesia, Ir. Sukarno in 1961. Bung Karno said: this nation must be built by prioritizing character building, because this character building will make Indonesia a great, advanced, and prosperous and dignified nation. This study is to find out the change in character of the prospective Civil Servants of the Ministry of Transportation of the second generation while participating in character development training in the HR Development Training Center for Human Resources Development. The research data was obtained by questionnaires given before (pretest) and after (posttest) the implementation of the training. This research is descriptive quantitative research. The results and discussion of this study is that there is a change in character in prospective Civil Servants of the transportation ministry after carrying out character building training. Changes in the character of participants in accordance with the learning agenda that is owned in accordance with the curriculum, namely: 1. Intrapersonal; 2. Interpersonal; 3. Professional relationship; 4. God relationship.